2006
DOI: 10.1074/jbc.m512818200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cardiac Fibrosis Induced by Urokinase Plasminogen Activator

Abstract: Human hearts with end-stage failure and fibrosis have macrophage accumulation and elevated plasminogen activator activity. However, the mechanisms that link macrophage accumulation and plasminogen activator activity with cardiac fibrosis are unclear. We previously reported that mice with macrophage-targeted overexpression of urokinase plasminogen activator (SR-uPA Cardiac fibrosis, the accumulation of excess extracellular matrix in the heart, is a common feature of end-stage heart disease independent of etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…Consistent with the findings we now report, Hertig and colleagues (30) reported that PAI-1 deficiency exacerbated fibrosis in a glomerular nephritis mouse model. Our findings are also consistent with those in cardiac injury, in which incremental uPA or decremental PAI-1 fosters cardiac fibrosis (31,32). Our data indicate that PAI-1 deficiency potentiates CBB-mediated pleural injury by exacerbating visceral pleural organization sufficient to worsen lung restriction.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with the findings we now report, Hertig and colleagues (30) reported that PAI-1 deficiency exacerbated fibrosis in a glomerular nephritis mouse model. Our findings are also consistent with those in cardiac injury, in which incremental uPA or decremental PAI-1 fosters cardiac fibrosis (31,32). Our data indicate that PAI-1 deficiency potentiates CBB-mediated pleural injury by exacerbating visceral pleural organization sufficient to worsen lung restriction.…”
Section: Discussionsupporting
confidence: 80%
“…For RA and possibly for osteoarthritis, my coinvestigators and I as well as other investigators have argued that uPA may be a therapeutic target, provided that the possible complication of persistent fibrin upon its blockade does not occur (1)(2)(3)9,24). Its inhibition may also have benefit, for example, in cancer metastasis (25), cardiac fibrosis (26), and lung inflammation (27). What is sorely needed for an understanding of the biology and pathology associated with the PA/plasmin system are potent and highly specific inhibitors of the PA activities that have the appropriate pharmacokinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Following bleomycin administration, the degree of hemorrhage and inflammation is reduced in uPAR−/− mice but no difference in fibrosis was detected compared with uPAR+/+ mice (113). In the heart uPAR deficiency does not prevent the fibrogenic effects of uPA-over-expression (126). While a large majority of the cellular and molecular mediators of fibrosis elicit similar effects in all of these organs, the uPA-uPAR family is a clear exception which highlights the need to carefully elucidate mechanisms of fibrosis under a variety of pathological states.…”
Section: Role Of Upa and Upar During Fibrogenesis: Disease And Organ mentioning
confidence: 91%